2019
DOI: 10.1126/science.aay7044
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, stable solar cells by using inherent bandgap of α-phase formamidinium lead iodide

Abstract: In general, mixed cations and anions containing formamidinium (FA), methylammonium (MA), caesium, iodine, and bromine ions are used to stabilize the black α-phase of the FA-based lead triiodide (FAPbI3) in perovskite solar cells. However, additives such as MA, caesium, and bromine widen its bandgap and reduce the thermal stability. We stabilized the α-FAPbI3 phase by doping with methylenediammonium dichloride (MDACl2) and achieved a certified short-circuit current density of between 26.1 and 26.7 milliamperes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
814
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,031 publications
(892 citation statements)
references
References 51 publications
17
814
2
Order By: Relevance
“…The reduced pseudo‐ total trap density can be further evaluated through SCLC model on hole‐only device of ITO/PEDOT:PSS/perovskite/spiro‐OMeTAD/Au. [ 61–63 ] The average trap densities determined from the dark current–voltage characteristics (hole‐only, Figure S18b, Supporting Information) based on Equation S2, Supporting Information, are 3.63 × 10 15 cm −3 and 2.56 × 10 15 cm –3 for the control and NMAI‐treated samples, respectively. The estimated results show that the surface trap density is reduced after NMAI treatment, which is well in line with the PL and TRPL measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The reduced pseudo‐ total trap density can be further evaluated through SCLC model on hole‐only device of ITO/PEDOT:PSS/perovskite/spiro‐OMeTAD/Au. [ 61–63 ] The average trap densities determined from the dark current–voltage characteristics (hole‐only, Figure S18b, Supporting Information) based on Equation S2, Supporting Information, are 3.63 × 10 15 cm −3 and 2.56 × 10 15 cm –3 for the control and NMAI‐treated samples, respectively. The estimated results show that the surface trap density is reduced after NMAI treatment, which is well in line with the PL and TRPL measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Perovskite solar cells (PSCs) based on organic–inorganic perovskites with 3D crystal structures have seen rapid progress in recent years, as demonstrated by the high power conversion efficiencies (PCE). [ 1,2 ] However, the intrinsic instability of 3D perovskite materials still remains unresolved. [ 3,4 ] Inert bulky organic cations can not only enhance their structural stability via strong interactions between covering organic cations and the [PbI 6 ] − units, but also block moisture from penetrating and corroding inner inorganic layers.…”
Section: Introductionmentioning
confidence: 99%
“…By using CuPC as hole transport layer (HTL), the MDACl 2 doped FAPbI 3 device exhibited higher humidity stability, retaining >90% of the initial PCE after 70 h under high humidity (85% RH, 25 °C), while the PCE of pure FAPbI 3 device reduced to 40% of the initial value (Figure 12f). [ 40 ] Besides the Cl based additive, Yu et al demonstrated an effective way to fabricate high‐quality FA based film by adding a small amount of lead thiocyanate [Pb(SCN) 2 ] to the precursor. The addition of Pb(SCN) 2 could effectively enlarge the grain size of FA 1− x Cs x PbI 3 perovskite film and significantly increased the carrier lifetime.…”
Section: Phase Stability Of Fapbi3‐based Solar Cellsmentioning
confidence: 99%
“…Reproduced with permission. [ 40 ] Copyright 2019, AAAS. g) PCE versus storage time of FAPbI 3 and FA 0.8 Cs 0.2 PbI 3 perovskite solar cells with and without 0.5 % Pb(SCN) 2 as additive, respectively.…”
Section: Phase Stability Of Fapbi3‐based Solar Cellsmentioning
confidence: 99%